Generalised muscle weakness in young adults with congenital heart disease. Issue 14 (21st January 2011) - Greutmann, Matthias; Le, Thao Lan; Tobler, Daniel; Biaggi, Patric; Oechslin, Erwin N; Silversides, Candice K; Granton, John T
Abstract : Background: In patients with heart failure from acquired cardiomyopathy, respiratory and skeletal muscle weakness is common and is an independent predictor for adverse events. Despite a different underlying pathology, many young adults with congenital heart disease (CHD) develop a syndrome comparable to heart failure from acquired cardiomyopathy and may be at risk for a similar skeletal muscle weakness. Objectives: To assess respiratory and skeletal muscle strength in adults with complex CHD. Methods: Respiratory and skeletal muscle function was assessed in 51 adults; 41 with complex CHD (16 tetralogy of Fallot, 11 univentricular anatomy with Fontan operation and 14 with subaortic right ventricles) and 10 controls. Maximal inspiratory (MIPs) and expiratory (MEPs) pressures, handgrip strength, lung volumes and aerobic capacity (peak VO2 ) were measured. Results: In patients with CHD (age 34±13 years), average% predicted MIPs, MEPs and handgrip strength were lower than in controls (77±27% vs 106±28%, 85±32% vs 116±41% and 72±15% vs 93±14%, respectively, p≤0.01). There was no significant difference in muscle weakness between CHD subgroups. In 39% of patients with CHD, the handgrip strength, and in 22%, respiratory muscle strength was <70% predicted. These patients had a significantly lower peak VO2 (50±12% vs 64±14% predicted, p=0.008). Conclusion: Respiratory and skeletal muscle weakness is common in young adults with complex CHD and similar to that found in older adults with advanced heart failure from acquired heart disease.